Analisis Pengaruh Perceived Usefulness, Ease of Use, dan Subjective Norm terhadap Impulsive Buying dengan Peran Attitude Sebagai Variabel Intervening: Studi pada Pengguna Aplikasi Tokopedia di Kota Semarang - Fadya Diva Irvanda; Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2025)
Tokopedia is one of the leading e-commerce platforms in Indonesia, holding the second position in terms of the number of visitors, after Shopee. However, in recent months, it has experienced a decline in users and received unfavorable ratings, which has potential to decrease their interest in shopping on Tokopedia, especially for impulsive purchases. This research aims to determine the influence of perceived usefulness, ease of use, and subjective norm on impulsive buying, with user attitude as an intervening variable among Tokopedia application users in Semarang City. Data from 185 respondents, selected using purposive sampling technique, were analyzed quantitatively and structurally using the Structural Equation Model (SEM) method with AMOS (Analysis of Moment Structures) 26. The results of the analysis indicate that perceived usefulness and subjective norm have a positive and significant effect on attitude. However, ease of use does not have a significant relationship with user attitude. Furthermore, attitude significantly and positively influences impulsive buying behavior. Therefore, Tokopedia should focus on enhancing the application's usefulness and leveraging external factors like subjective norms to shape user attitudes, ultimately encouraging more impulsive purchases on its platform.